PENGARUH LINGKUNGAN KERJA DAN MOTIVASI SERTA KOMPENSASI TERHADAP SEMANGAT KERJA PEGAWAI DINAS KESEHATAN KABUPATEN TABANAN - Jaya, I Gde Made Kusuma; Sudibya, I Gde Adnyana; Sudharma, I Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
Work environment, motivation, and compensation is an important thing to consider in retaining and attracting qualified human resources. This study aims to demonstrate empirically the effect of the work environment, work motivation, and compensation for employee morale in Tabanan District Health Office. The sampling method used in this research is total sampling method with a sample of 85 respondents. This study uses primary data by distributing questionnaires as a means of testing the hypothesis. Secondary data as a complement to the data used is the budget and actual performance of employees in Tabanan District Health Office in 2015. The analysis technique used in this research is Multiple Regression Analysis. Prior to test hypotheses, first tested the validity and reliability, the classic assumption test and assess the goodness of fit regression model. The results showed that the working environment a significant effect on employee morale. Motivation significant effect on employee morale. Compensation significant effect on employee morale in Tabanan District Health Office
Keywords: work environment, motivation, compensation, employee morale